2015
DOI: 10.1007/978-981-287-408-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Criteria for Creating Online Educational Games for Seniors

Abstract: What do we know about the ergonomic criteria that are needed to create an effective online educational game for seniors? A literature review was conducted as part of a development project to flesh out a number of issues: How can game component design be adapted to accommodate seniors' physical or intellectual limitations? How should a game interface and its components be displayed on the screen to facilitate game navigation? What restrictions should be considered when selecting computer game equipment to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…For instance, considering older adults' declines in perception and sensation, decisions to use visual presentations such as reflective, decorative or animated images should be made cautiously (Namba et al, 1995 ; Green and Bavelier, 2003 ). Other design principles regarding auditory feedback (Charness and Jastrzembki, 2009 ; Fisk et al, 2009 ), haptic feedback (Lee and Kuo, 2001 ; Harada et al, 2013 ), and memory assistance (Ferreira and Pithan, 2005 ; Fisk et al, 2009 ; Sauve et al, 2015 ) have also been reported in related studies. According to this review, the present study proposes five principles that should be considered during the development of the interface and interaction in a digital game for the cognitive training of elderly people: (1) Provide clear and multisensory game instructions and suitable interaction.…”
Section: Introductionmentioning
confidence: 84%
“…For instance, considering older adults' declines in perception and sensation, decisions to use visual presentations such as reflective, decorative or animated images should be made cautiously (Namba et al, 1995 ; Green and Bavelier, 2003 ). Other design principles regarding auditory feedback (Charness and Jastrzembki, 2009 ; Fisk et al, 2009 ), haptic feedback (Lee and Kuo, 2001 ; Harada et al, 2013 ), and memory assistance (Ferreira and Pithan, 2005 ; Fisk et al, 2009 ; Sauve et al, 2015 ) have also been reported in related studies. According to this review, the present study proposes five principles that should be considered during the development of the interface and interaction in a digital game for the cognitive training of elderly people: (1) Provide clear and multisensory game instructions and suitable interaction.…”
Section: Introductionmentioning
confidence: 84%
“…Although some earlier research has found that embedding learning content in digital games has limited potential, as it does not leverage the more powerful learning mechanics of games (Clark et al, 2014;Young et al, 2012), our study showed the contrary. This is perhaps because our digital game is a ''frame'' game specifically designed to support learning (Sauve´, 2005), has embedded a number of motivational elements, and has been designed specifically for this target audience (Sauve´et al, , 2015a(Sauve´et al, , 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…The Bingo Nutrition and Health game chosen for this study is a replica of traditional Bingo that has been digitized as a multiplayer online game and extended into a “frame game”—an educational game template that allows the input of questions, with feedback, to embed learning on any desired topic into the gameplay (Sauvé, 2005). Our team developed this game following a user-centered design process, applying ergonomic principles that were appropriate for the older adult audience (Sauvé, Renaud, Duplàa, & Kaufman, 2014; Sauvé, Renaud, Kaufman, & Duplàa, 2015a, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…Другие принципы выбора компьютерных программ касаются учета особенностей слуховой обратной связи, тактильной обратной связи и наличия подсказок для памяти (Binder et al, 2015;Harada, Sato, Takagi, & Asakawa, 2013;Sauve, Renaud, Kaufman, & Duplaa, 2015;Werner, Werner, & Oberzaucher, 2012). Согласно представленным работам, предлагается пять основных принципов, которые следует учитывать при выборе и применении программ для когнитивного обучения пожилых пациентов с когнитивными нарушениями:…”
Section: теоретическое обоснованиеunclassified